Effectiveness of Science (Physics) Teacher Training Program on Conceptual Understanding at MTs Manado - Hasan, Nailul; Aruan, Nenni Mona; Fauzyah, Nur Aini (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
This study aims to evaluate the effectiveness of the physics science teacher training program in improving the understanding of physics concepts at one of the Madrasah Tsanawiyah (MTs) in Manado. Using pre-test and post-test data from 52 teachers, the Wilcoxon Signed-Rank Test was analyzed. The results showed significant improvement in trainees' understanding of physics concepts, with a p-value of 0.0004 and a large effect size (r = 0.60). These findings provide empirical evidence that the training is effective in improving teachers' conceptual understanding and can be used as a basis for developing similar programs in other regions.